In vitro enantioselective inhibition of the main human CYP450 enzymes involved in drug metabolism by the chiral pesticide tebuconazole - Habenschus, Maísa Daniela; Carrão, Daniel Blascke; de Albuquerque, Nayara Cristina Perez; Perovani, Icaro Salgado; Moreira da Silva, Rodrigo; Nardini, Viviani; Lopes, Norberto Peporine; Dias, Luís Gustavo; Moraes de Oliveira, Anderson Rodrigo [UNESP] (Elsevier, 2021)
Tebuconazole (TEB) is a chiral triazole fungicide worldwide employed to control plant pathogens and preserve wood. People can be exposed to TEB either through diet and occupational contamination. This work investigates the in vitro inhibitory potential of rac-TEB, S-(+)-TEB, and R-(−)-TEB over the main cytochrome P450 enzymes (CYP450) using human liver microsomes to predict TEB in vivo inhibition potential. The IC50 values showed that in vitro inhibition was enantioselective for CYP2C9, CYP2C19, and CYP2D6, but not for CYP3A4/5. Despite enantioselectivity, rac-TEB and its single enantiomers were always classified in the same category. The inhibition mechanisms and constants were determined for rac-TEB and it has shown to be a mixed inhibitor of CYP3A4/5 (Ki = 1.3 ± 0.3 μM, αKi = 3.2 ± 0.5 μM; Ki = 0.6 ± 0.3 μM, αKi = 1.3 ± 0.3 μM) and CYP2C9 (Ki = 0.7 ± 0.1 μM, αKi = 2.7 ± 0.5 μM), and a competitive inhibitor of CYP2D6 (Ki = 11.9 ± 0.7 μM) and CYP2C19 (Ki = 0.23 ± 0.02 μM), respectively, suggesting that in some cases, rac-TEB has a higher or comparable inhibitory potential than well-known strong inhibitors of CYP450 enzymes, especially for CYP2C9 and CYP2C19. In vitro-in vivo extrapolations (IVIVE) were conducted based on the results and data available in the literature about TEB absorption and metabolism. R1 values were estimated based on the Food and Drug Administration guideline and suggested that in a chronic oral exposure scenario considering the acceptable daily intake dose proposed by the European Food and Safety Authority, the hypothesis of rac-TEB to inhibit the activities of CYP3A4/5, CYP2C9, and CYP2C19 in vivo and cause pesticide-drug interactions cannot be disregarded.
Keywords: Chiral; Cytochrome P450; Enantioselective; Human liver microsomes; Inhibition; Tebuconazole